Sequence-specific hypomethylation of the tobacco genome induced with dihydroxypropyladenine, ethionine and 5-azacytidine - Kovarík, A; Koukalová, B; Holý, A; Bezdĕk, M (FEBS letters, 1994)
Higher plant DNA is methylated at CG and CNG targets. In this study we have investigated the tobacco methylation system in tissue culture using the methylation inhibitors 5-azacytidine (5-azaC), dihydroxypropyladenine (DHPA) and ethionine (Ethi), and methylation-sensitive restriction endonucleases HpaII, MspI, HhaI, EcoRII, ScrFI, and Fnu4HI. Surprisingly, CAG/CTG sequences, contrary to CG doublets and CCG/CGG triplets, appeared to be refractory to the inhibitory effect of 5-azaC. Thus 5-azaC cannot be considered a general inhibitor of DNA methylation in tobacco cells. On the other hand, DHPA, the inhibitor of S-adenosylhomocysteine (SAH) hydrolase, and Ethi caused hypomethylation of both CAG/CTG and CCG/CGG triplets but not of the CG doublets. The sensitivity of triplet-specific methylation to the inhibition of SAH hydrolase suggests the possibility that plant-specific DNA methylation at CNG targets might be modulated by alterations of the SAH/S-Adenosylmethionine ratio in plant cells.
Keywords: kultivované buňky; Cells, Cultured; Plants, Toxic; ethionin; Methylation; Adenosylhomocysteinase; cytosin-specifické DNA-methylasy; DNA rostlinná; tabák; Genome, Plant; Adenine; adenin; azacytidin; Hydrolases; hydrolasy; Deoxyribonucleases, Type II Site-Specific; Ethionine; Nicotiana; restrikční endonukleasy typu II; Azacitidine; metylace; DNA, Plant; DNA-Cytosine Methylases; genom rostlinný; jedovaté rostliny; adenosylhomocysteinasa